First Serologic Analysis of Antibodies Against African Swine Fever Virus Detected in Domestic Pig Farms in South Korea from 2019 to 2024 - Seong-Keun Hong; Mugyeom Moon; Ki-Hyun Cho; Hae-Eun Kang; Jong-Soo Lee; Yeon-Hee Kim (Pathogens, 2025)
Background: African swine fever (ASF) is a crucial socioeconomic setback to South Korea’s swine industry. This study aimed to determine seropositivity for ASF virus (ASFV) in pigs that appeared to be infected on farms with reported ASF outbreaks. Methods: A total of 2232 sera from ASF outbreaks (2019–2024) in South Korea were collected. Two enzyme-linked immunosorbent assay (ELISA) kits were used to detect ASFV antibodies, and an immunoperoxidase test (IPT) was used as a confirmatory test following the method recommended by the World Organisation for Animal Health in the Manual of Diagnostic Tests and Vaccines for Terrestrial Animals. Also, spatial clustering was identified using the Density-Based Spatial Clustering of Applications with Noise (DBSCAN) model to understand ASF hotspots in the wild boar population and assess the spatial relationship between the hotspots and ASF antibody-positive domestic pig farms. Results: Antibodies were first detected in Hwacheon in 2020, but by 2024, only 1.43% of pigs had detectable antibodies against ASFV. Although this percentage is still low, the number of antibody-positive pigs is gradually increasing. Additionally, 32 positive samples were found from nine pig farms with outbreaks, and these samples were confirmed positive in both the two ELISA tests and the IPT. The highest seropositivity was recorded at the finishing stage of pig production. When compared to the confirmatory IPT, both blocking and competition ELISA demonstrated high diagnostic sensitivities. The statistical association between ASF antibody-positive farms and wild boars were analyzed using Fisher’s exact test, yielding a significant p-value of 0.007. This indicates a strong correlation, as eight out of nine ASF-seropositive farms were located within hotspots that were significantly associated. Conclusions: Our findings provide valuable insights into ASFV antibody detection in South Korea and demonstrate a statistical association between farms housing pigs with ASFV antibodies and hotspots of ASFV-infected wild boars. Confirmatory tests, such as the IPT, are needed. These insights will contribute to the improvement of surveillance and biosecurity measures for swine farms.